Optimizing Human Resources Management at PT. Sritex With Business Intelligence - Faeni, Dewi Puspaningtyas; Rahma, Sofie Aura (LANCAH: Jurnal Inovasi dan Tren, 2024)
PT Sri Rejeki Isman Tbk (Sritex), one of Indonesia's largest textile companies, is facing significant Human Resource Management (HRM) challenges. To address these challenges, Sritex has started utilizing Business Intelligence (BI) technology to optimize their HRM practices and improve operational efficiency, productivity, and employee satisfaction. This study aims to explore the application of BI in HRM at Sritex and identify the positive impacts it brings. BI is a technology that collects, integrates, analyzes, and presents business data to support decision-making. With BI, Sritex can manage employee data more efficiently, conduct in-depth performance analysis, and make accurate workforce planning. The research findings show that implementing BI at Sritex has several benefits. It enhances recruitment efficiency, allows for more targeted employee development, enables accurate performance assessments, and facilitates competitive compensation. Additionally, BI helps in real-time monitoring and evaluation of employee performance, allowing management to take prompt actions to improve productivity and efficiency. However, there are challenges such as resistance to change and significant investment requirements that arise during the implementation process. This research provides valuable insights for Sritex and other textile companies facing similar HRM challenges. By applying BI technology, these companies can enhance their competitiveness in the global market through more effective and efficient HRM practices.